Ligilactobacillus salivarius Strains Isolated From the Porcine Gut Modulate Innate Immune Responses in Epithelial Cells and Improve Protection Against Intestinal Viral-Bacterial Superinfection - Indo, Yuhki; Kitahara, Shugo; Tomokiyo, Mikado; Araki, Shota; Islam, Md. Aminul; Zhou, Binghui; Albarracin, Leonardo; Miyazaki, Ayako; Ikeda-Ohtsubo, Wakako; Nochi, Tomonori; Takenouchi, Takato; Uenishi, Hirohide; et al. (Frontiers in Immunology, 2021)
Previously, we constructed a library of Ligilactobacillus salivarius strains from the intestine of wakame-fed pigs and reported a strain-dependent capacity to modulate IFN-β expression in porcine intestinal epithelial (PIE) cells. In this work, we further characterized the immunomodulatory activities of L. salivarius strains from wakame-fed pigs by evaluating their ability to modulate TLR3- and TLR4-mediated innate immune responses in PIE cells. Two strains with a remarkable immunomodulatory potential were selected: L. salivarius FFIG35 and FFIG58. Both strains improved IFN-β, IFN-λ and antiviral factors expression in PIE cells after TLR3 activation, which correlated with an enhanced resistance to rotavirus infection. Moreover, a model of enterotoxigenic E. coli (ETEC)/rotavirus superinfection in PIE cells was developed. Cells were more susceptible to rotavirus infection when the challenge occurred in conjunction with ETEC compared to the virus alone. However, L. salivarius FFIG35 and FFIG58 maintained their ability to enhance IFN-β, IFN-λ and antiviral factors expression in PIE cells, and to reduce rotavirus replication in the context of superinfection. We also demonstrated that FFIG35 and FFIG58 strains regulated the immune response of PIE cells to rotavirus challenge or ETEC/rotavirus superinfection through the modulation of negative regulators of the TLR signaling pathway. In vivo studies performed in mice models confirmed the ability of L. salivarius FFIG58 to beneficially modulate the innate immune response and protect against ETEC infection. The results of this work contribute to the understanding of beneficial lactobacilli interactions with epithelial cells and allow us to hypothesize that the FFIG35 or FFIG58 strains could be used for the development of highly efficient functional feed to improve immune health status and reduce the severity of intestinal infections and superinfections in weaned piglets.